Resist - Book 2 - Crossan, Sarah; Crossan, Sarah (New York, New York : Greenwillow Books, an imprint of HarperCollinsPublishers, 2013)
Alina, Quinn, and Bea, now outlaws and outcasts, make their way to the last enclave of the Resistance but once there, they discover they can count on no one but each other and may, in fact, have to betray those they considered allies.
HL640
Accelerated Reader
Keywords: Survival -- Juvenile fiction; Insurgency -- Juvenile fiction; Environmental degradation -- Juvenile fiction; Shipwreck survival -- Fiction; Insurgency -- Fiction; Environmental degradation -- Fiction; Adventure stories; Science fiction; Childrens stories -- Action & Adventure; Survival Stories; Childrens stories -- Science & Technology; Childrens stories -- Love & Romance; Survival -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction; Science fiction